Factors Contributing to Online Purchase Intention amongst Malaysian Consumers: A Case of Lazada - Friday Ogbu Edeh; Majdi Anwar Quttainah; Syarifah Nurdzamanisya Syed Badrulzaman; Daisy Mui Hung Kee; Syafiqah Mohd Zamri; Tahreem Tariq Mahmud; Siti Syafiqah Izni Shafiee; Victory Chinelo Awoke (AIBPM Publisher, 2021)
Online shopping activity amongst Malaysians increase unexpectedly ever since Malaysia had its first phase of Movement Control Order. In other words, the global pandemic COVID-19 provided more opportunities for e-commerce such as Lazada to grow. Therefore, this study intends to understand the factors that contribute to online purchase intention amongst Malaysians in the case of Lazada. This study used qualitative and quantitative method. The questionnaire used to collect the data from the respondents. There are 100 Malaysians that had previously purchased from Lazada have participated in the survey. The results showed that there is a positive correlation between product quality, product price, buying experience, after-sales service, and online consumer satisfaction.